1968
DOI: 10.1002/bjs.1800550411
|View full text |Cite
|
Sign up to set email alerts
|

Effect of common bile-duct transplantation on gastric acid secretion in the dog

Abstract: THE surgical management of traumatic stricture of the common bile-duct involves a choice, when direct repair is impractical, between two operations : choledochojejunostomy (Cole, Ireneus, and Reynolds, 1951) and choledochoduodenostomy (Capper, 1961; FIG. :.-A, Choledochoiejunostomy. 6 , Choledochoduodenostomy. C, Choledochodochostom Through-and-through ooooo silk sutures were used without t d e s or splints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
2

Year Published

1971
1971
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 11 publications
0
4
0
2
Order By: Relevance
“…Experimentally, cholecystojejunostomy has been found to be associated with gastric ulceration due to impairment of inhibitory control over gastric acid production by the duodenum. 17,19 Duodenal ulceration can occur because bile, which is mildly alkaline, is not present to neutralise gastric acid as it enters the duodenum. 10 Despite experimental evidence there are no case reports in the literature that confirm this sequela in dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Experimentally, cholecystojejunostomy has been found to be associated with gastric ulceration due to impairment of inhibitory control over gastric acid production by the duodenum. 17,19 Duodenal ulceration can occur because bile, which is mildly alkaline, is not present to neutralise gastric acid as it enters the duodenum. 10 Despite experimental evidence there are no case reports in the literature that confirm this sequela in dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this finding, Menguy (1961) insisted that hypersecretion of gastric acid after cholecystoileostomy (Roux-en-Y) should be attributed to some factors other than loss of intestinal inhibition related to indigestion of fat due to the interrupted bile flow into the duodenum. Breen et al (1968) performed choledochojejunostomy (Roux-en-Y) in 12 dogs with Heidenhain pouch, and found an increase in gastric acid secretion. Furthermore, hypersecretion of gastric acid was significant early on the 5th day of operation in 4 to 5 dogs with cholecystojejunostomy (Roux-en-Y), contrasted with no increase of the secretion in dogs with cholecystoduodenostomy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent experimental evidence indicates that the biliary secretion of bicarbonate makes only a negligible contribution to duodenal buffering of acid [K o n t u re k , 1971]. It does not, for instance, explain the gastric hypersecretion observed in experimental animals after biliary diversion [Breen et al, 1968], although other studies suggest that this concept is at least debatable since in certain animal species diversion of bile did not evoke a change in basal acid output [K o On several occasions hepatic damage has been pointed out to be an important etiological factor. It also has been shown that gastric hypersecre tion, resulting from biliary tract obstruction, persists after decompressing the bile ducts, if irreversible liver damage has occurred [Silen et al, 1963], Repeatedly, the diminished ability of the liver to destroy histamine, absorbed from the intestine, has been blamed for this phenomenon [Anrep and Barsoum , 1953].…”
mentioning
confidence: 98%